PERSAMAAN AKUNTANSI DALAM TRANSAKSI BISNIS - Ulfah, Almira Keumala (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
This study intends to analyze comprehensively about accounting equations in business transactions. The accounting equation is the basis for understanding accounting records that use paired records so that the amount of debit is always balanced with credit and can know where the position of assets, debt position and capital position in each transaction. The basic accounting equation is an equation that shows the balance between assets, liabilities, and equity. The basic accounting equation is an equation that shows the balance between assets, liabilities, and equity. The accounting equation does not only record transactions that are directly related to assets, debt and capital. The accounting equation can also be used to see the effects of income, expenditure, expense, and transaction transactions. Therefore, before making financial statements we must first have to understand the basic concept of accounting, the accounting equation. The basic equation in accounting is a basic concept in making financial statements. Keywords: accounting equations, financial statements, and business transactions Abstrak Penelitian ini bermaksud untuk menganalisis secara komprehensif tentang persamaan akuntansi dalam transaksi bisnis. Persamaan akuntansi merupakan dasar untuk memahami pencatatan akuntansi yang menggunakan catatan berpasangan sehingga besarnya debit selalu seimbang dengan kredit dan dapat diketahui dimana posisi aset, posisi hutang dan posisi modal dalam setiap transaksi. Persamaan akuntansi dasar adalah persamaan yang menunjukkan keseimbangan antara aset, kewajiban, dan ekuitas. Persamaan akuntansi dasar adalah persamaan yang menunjukkan keseimbangan antara aset, kewajiban, dan ekuitas. Persamaan akuntansi tidak hanya mencatat transaksi yang berhubungan langsung dengan aset, hutang dan modal. Persamaan akuntansi juga dapat digunakan untuk melihat pengaruh pendapatan, pengeluaran, pengeluaran, dan transaksi transaksi. Oleh karena itu, sebelum membuat laporan keuangan kita terlebih dahulu harus memahami konsep dasar akuntansi yaitu persamaan akuntansi. Persamaan dasar dalam akuntansi merupakan konsep dasar dalam pembuatan laporan keuangan. Kata kunci: persamaan akuntansi, laporan keuangan, dan transaksi bisnis